Techniques for randomization and allocation for clinical trials - Miola, Anna Carolina [UNESP]; Espósito, Ana Cláudia Cavalcante; Miot, Hélio Amante [UNESP] (My University, 2024)
Intervention studies require all participants to originate from the same population, with random allocation to intervention groups to ensure comparability. Randomization is crucial for minimizing confounding factors, allowing differences in outcomes to be attributed to the intervention. Simple randomization performs well for large samples (>100 per group), but smaller samples may require block or stratified randomization to balance group sizes and covariates. When randomization isn't feasible, quasi-randomized methods (e.g., based on dates or enrollment order) can help but must compensate with multivariate adjustments. Moreover, blinding and allocation concealment enhance internal validity and reproducibility. Allocation concealment (e.g., sealed envelopes) prevents bias during participant assignment while blinding mitigates detection and performance biases. Precise methodological descriptions in clinical trial registrations and publications enhance study reliability and reproducibility, highlighting the importance of rigorous planning and transparent reporting in intervention research. This article reviews the key concepts of randomization, blinding, and allocation concealment in interventional studies.
Técnicas de randomização e alocação para estudos clínicos
Keywords: Allocation Concealment; Bias Reduction; Intervention Studies; Methodological Validity; Randomization